You are on page 1of 8

2-D vector rocket equations with air drag

1. Burnout time
The average mass of the rocket during boost is

mP
(1.1) mA = mD +
2

mA = Average mass [ kg ]
mD = Rocket dry mass [ kg ]
mP = Propellant mass [ kg ]

The coast mass is equal to the rocket dry mass.

The air drag FD for the rocket is given by

1
(1.2) FD = k ⋅ vt2B = ⋅ ρ ⋅ CDR ⋅ AR
2

m
vtB = Burnout velocity [ ]
s
kg
ρ = Air density [ ]
m3
CDR = Drag coefficient of the rocket [-] (0.75 for average rockets)
AR = Rocket cross-sectional area [ m 2 ]

The thrust of the rocket FT is then

(1.3) FT = T − mA ⋅ g − k ⋅ vt2B

T = Motor thrust [ N ]
m
g = Acceleration of gravity [ ]
s2

The definition of force is

(1.4) F = m ⋅ a

M.B. Nov. 22/2010 1


As the mass is constant the factor rule in differentiation allows the mass to move outside
the derivative operator, and the equation becomes

dv
(1.5) F = m ⋅
dt

dv
(1.6) mA ⋅ = T − mA ⋅ g − k ⋅ v 2
dt

dv
(1.7) mA ⋅ = T − mA ⋅ g − k ⋅ v 2
dt

mA ⋅ dv mA ⋅ dv
(1.8) dt = =
T − mA ⋅ g − k ⋅ v 2
T − mA ⋅ g
k⋅ − k ⋅ v2
k
T − mA ⋅ g
Substituting x 2 = yields to
k

mA ⋅ dv m dv
(1.9) dt = = A⋅ 2 2
k ⋅ x − k ⋅v
2 2
k x −v

To get now the burnout time t B , we integrate over vtB

mA  1 
k ∫  x2 − v2  B
(1.10) t B = ⋅  dvt

mA ln( x + vtB ) − ln(vtB − x)


(1.11) t B = ⋅ +C
k 2x

With the condition t B = 0 (and thus vtB = 0 ) we can determine the integration constant
C:

mA ln( x) − ln(− x)
(1.12) ⋅ +C = 0
k 2x

mA ln(− x) − ln( x)
(1.13) C = ⋅
k 2x

(1.14)
m ln( x + vtB ) − ln(vtB − x) mA ln(− x) − ln( x)
tB = A ⋅
k 2x
+
k

2x
=
mA
2⋅k ⋅ x
(
⋅ ln( x + vtB ) − ln(vtB − x) + ln(− x) − ln( x) )

M.B. Nov. 22/2010 2


(1.15)
mA ln( x + vtB ) − ln(vtB − x) mA ln(− x) − ln( x) mA   x + vtB   −x  
tB = ⋅ + ⋅ = ⋅  ln   + ln   
k 2x k 2x 2 ⋅ k ⋅ x   x  v
 Bt − x 

mA  x + vtB 
(1.16) t B = ⋅ ln   Burnout time equation
2 ⋅ k ⋅ x  x − vtB 

2. Burnout velocity

Solving now for vtB :

2⋅k ⋅ x  x + vtB 
(1.17) ⋅ t B = ln  
mA  x − vt
 B 

2⋅k ⋅ x
Substitution y =
mA

 x + vtB 
(1.18) y ⋅ t B = ln  
 x − vt
 B 

x + vtB
(1.19) e y ⋅tB =
x − vtB

(1.20) x ⋅ e y⋅tB − x = vtB (1 + ⋅e y⋅tB )

e y⋅tB − 1
(1.21) vtB = x ⋅ Burnout velocity equation
e y⋅tB + 1

The burnout time t B can be also written as

I sp ve
tB = =
T g ⋅T

I sp = Specific impulse [ s ]

M.B. Nov. 22/2010 3


m
ve = Effective exhaust velocity [ ]
s

3. Burnout altitude

To get now the burnout velocity hB we need to integrate 1.21 over the burnout time:

 e y⋅t − 1  2 ⋅ x ⋅ ln ( e y⋅tB + 1) − t B ⋅ x ⋅ y
(1.22) hB = ∫  x ⋅ y⋅t dt B = +C
 e +1  y

2 ⋅ x ⋅ ln ( e y⋅tB + 1) − t B ⋅ x ⋅ y
(1.23) hB = +C
y

With the condition hB = 0 (and thus t B = 0 ) we can determine the integration constant
C:

2 ⋅ x ⋅ ln ( 2 )
(1.24) +C = 0
y

2 ⋅ x ⋅ ln ( 2 )
(1.25) C = −
y

2 ⋅ x  e y⋅tB + 1 
(1.26) hB = ⋅ ln   − tB ⋅ x
y  2 

2⋅k ⋅ x
Substitution y =
mA

mA  e y⋅tB + 1 
(1.27) hB = ⋅ ln   − tB ⋅ x Burnout altitude equation 1
k  2 

Replacing e y ⋅tB by

x + vtB
(1.28) = e y⋅tB
x − vtB

yields to

M.B. Nov. 22/2010 4


mA  x 
(1.29) hB = ⋅ ln   − t B ⋅ x
k  x − vt
 B 

mA  x + vtB 
(1.30) t B = ⋅ ln  
2 ⋅ k ⋅ x  x − vtB 

mA  x   mA  x + vtB 
(1.31) hB = ⋅ ln   −  ⋅ ln    ⋅ x
 x − vt   
k  B   2 ⋅ k ⋅ x  x − vtB 

mA  x  mA  x + vtB 
(1.32) hB = ⋅ ln   − ⋅ ln  
 x − vt  x − vt
k  B  2⋅k  B 

2 ⋅ mA  x  mA  x + vtB 
(1.33) hB = ⋅ ln   − ⋅ ln  
2⋅k  x − vt  x − vt
 B  2⋅k  B 

2
m  x  m  x + vtB 
(1.34) hB = A ⋅ ln   − A ⋅ ln  
2⋅k  x − vt
 B  2⋅k  x − vtB 

 x − vtB 
mA  x2
(1.35) hB = ⋅ ln ⋅
2⋅k  x−v
( ) x + vtB 
2

 tB 

mA  x2 
(1.36) hB = ⋅ ln  2 2  Burnout altitude equation 2
2⋅k  x − vt
 B 

4. Coasting altitude

After the rocket has reached the burnout altitude, the so called coasting phase begins. The
rocket has then the dry mass mD and the initial velocity vtB . To derive the coast altitude
hC we start again with the definition of force:

dv
(1.37) F = m ⋅ a = m ⋅ v ⋅
dh

M.B. Nov. 22/2010 5


dv
(1.38) mD ⋅ v ⋅ = −mD ⋅ g − k ⋅ v 2
dh

mD ⋅ v ⋅ dv
(1.39) dh =
−mD ⋅ g − k ⋅ v 2

mD ⋅ v ⋅ dv
(1.40) dh =
− mD ⋅ g
k⋅ − k ⋅ v2
k

−mD ⋅ g
Substitution z 2 =
k

mD v ⋅ dv
(1.41) dh = ⋅
k z2 − v2

mD v ⋅ dv
(1.42) dh = ⋅
k z2 − v2

mD  v 
k ∫  z 2 − v2  B
(1.43) hC = ⋅  dvt

mD  vtB 
(1.44) hC =
k  z − vt 
m
2⋅k
(
⋅ ∫  2 2 dvtB = D ⋅ ln z 2 − vt2B + C )
 B 

With the condition hC = 0 (and thus vtB = 0 ) we can determine the integration constant
C:

⋅ ln ( z 2 ) + C = 0
mD
(1.45)
2⋅k

⋅ ln ( z 2 )
mD
(1.46) C = −
2⋅k

(1.47) hC =
mD
2⋅k
( )
⋅ ln z 2 − vt2B − D ⋅ ln ( z 2 )
m
2⋅k

mD  z 2 − vt2B 
(1.48) hC = ⋅ ln   Coast altitude equation
2⋅k  z2
 

M.B. Nov. 22/2010 6


5. Coast time

To determinate the time tC from vtB to 0 (coasting time), the starting point is again the
definition of force. The acceleration is here negative:
 dv 
(1.49) F = m ⋅ ( − a ) = m ⋅  − 
 dt 

 dv 
(1.50) mC ⋅  −  = − mC ⋅ g − k ⋅ v 2
 dt 

dv
(1.51) dt = mC ⋅
mC ⋅ g + k ⋅ v 2

dv
(1.52) dt = mC ⋅
m ⋅g
k ⋅ C + k ⋅ v2
k

mC ⋅ g
Substitution za 2 =
k

mC dv
(1.53) dt = ⋅ 2 2
k za + v

 vt 
arctan  B 
m  1  m  za  +C
(1.54) tC = C ⋅ ∫  2 2 dvtB = C ⋅
k  za + v  k za

With the condition tC = 0 (and thus vtB = 0 ) we can determine the integration constant
C:

0 
arctan  
m
(1.55) C ⋅  za  +C = 0⇒C = 0
k za

mC  vt 
(1.56) tC = ⋅ arctan  B  Coast time equation
k ⋅ za  za 

M.B. Nov. 22/2010 7


6. Parachute size

m
The desired maximum decent velocity for a rocket is 3-5 . Therefore the parachute size
s
needs to be accordingly calculated.

The maximum velocity vE is then reached if the acceleration a = 0 , hence

1
(1.57) F = m ⋅ a = 0 = mD ⋅ g − ⋅ CDP ⋅ ρ ⋅ AP ⋅ v 2
2

2 ⋅ mD ⋅ g
(1.58) vE =
CDP ⋅ ρ ⋅ AP

CDP = Drag coefficient of the rocket [-] (0.75 for a flat sheet used for a parachute, or 1.5
for a true dome-shaped chute).
AR = Parachute area [ m 2 ]

Solving for AP :

2 ⋅ mD ⋅ g
(1.59) AP =
vE2 ⋅ CDP ⋅ ρ

π ⋅ DP2
The chute area is AP = , so the chute diameter is
4

8 ⋅ mD ⋅ g
(1.60) DP = Parachute diameter equation
π ⋅ vE2 ⋅ CDP ⋅ ρ

M.B. Nov. 22/2010 8